Correlation between the Leaflet–Annulus Index and Echocardiographic Indices in Maltese Dogs with Myxomatous Mitral Valve Disease - Han-Joon Lee; Hyung-Jin Park; Joong-Hyun Song; Kun-Ho Song (Veterinary Sciences, 2023)
Myxomatous mitral valve disease (MMVD) is the most common chronic heart valve disease, leading to left-sided cardiomegaly in dogs. The leaflet–annulus index (LAI) was originally used in humans as a predictor of mitral regurgitation (MR) after mitral valve repair surgery. This index represents the quantity and severity of MR since it is affected by annular dilation. Recently, LAI was adapted to veterinary medicine, and its usefulness as an indicator of annular dilation on 2D transthoracic echocardiography in MMVD dogs was suggested. For this study, 135 Maltese dogs were selected and divided into groups of control, B1, and B2, according to the American College of Veterinary Internal Medicine consensus statement. The following data were collected: radiographic indices including the vertebral heart score and vertebral left atrial size, echocardiographic indices including the left-atrium-to-aortic-root ratio (LA:Ao), left ventricular internal diameter at diastole, normalized for body weight, and anteroposterior length and LAI measured on right parasternal long-axis view. The results showed a significant difference in LAI between each group, becoming smaller as the disease progressed. Also, there was a significant correlation between LAI and each index, showing the strongest correlation with LA:Ao. LAI could be helpful as a new indicator used for the determination of severity and prognosis in Maltese dogs with MMVD.